2019
DOI: 10.1016/j.sjbs.2019.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between HIF-1α and apoptosis in rats with traumatic brain injury and the influence of traditional Chinese medicine Sanqi

Abstract: Objective To explore the expression of HIF-1α, neuronal apoptosis and the influence of traditional Chinese medicine Sanqi on hematoma after brain injury in rats. Methods Ninety SD rats were divided into 3 groups randomly: blank control group, traumatic brain injury (TBI) group and Sanqi intervention group, and they were decapitated after brain injury at different time points: 6 h, 1 d, 2 d, 3 d, 5 d, 7 d. The model of cerebral hemorrhage was made by autologous non-coagulation in stereotactic locator, the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…may be in part responsible for ischemia and reperfusion brain injury in clinical settings (Guan et al, 2020). Previous studies support that metabolic dysfunction (oxygen and glucose deprivation, and restoration), inflammation, and immune response are the main physiopathological mechanisms of CI/R (Jin et al, 2018;Yang et al, 2019). Our study found that the significantly changed proteins were mostly related to the immune response as well as metabolic pathways, which was similar to previous work.…”
Section: Discussionsupporting
confidence: 92%
“…may be in part responsible for ischemia and reperfusion brain injury in clinical settings (Guan et al, 2020). Previous studies support that metabolic dysfunction (oxygen and glucose deprivation, and restoration), inflammation, and immune response are the main physiopathological mechanisms of CI/R (Jin et al, 2018;Yang et al, 2019). Our study found that the significantly changed proteins were mostly related to the immune response as well as metabolic pathways, which was similar to previous work.…”
Section: Discussionsupporting
confidence: 92%
“…At present, the methods for treatment of TBI include stem cell transplantation [47,48], injection of growth factors [49,50], traditional Chinese medicine treatment, etc. [51][52][53]. However, the low survival rate and differentiation efficiency after stem cell transplantation, the short half-life of growth factors, and the difficulty of traditional Chinese medicine in crossing the blood-brain barrier limit their therapeutic effects.…”
Section: Discussionmentioning
confidence: 99%